Kritik Atas Peraturan Wali Nikah Dalam KHI dan Fikih Perspektif Gender - Is Ashidiqie, Mughni Labib Ilhamuddin (UIN Sunan Kalijaga Yogyakarta, 2021)
The guardian is one of the pillars that must be fulfilled in marriage contract. In its practice, it is deemed necessary for reconstruction due to the provisions of marriage guardian stipulated in Article 20 Paragraph (1) in Islamic Law Compilation reflect provisions that are gender biased and irrelevant to conventions ratified by the Indonesia government, because only men’s right to be marriage guardian. This article is intended to critically examine the provisions of the guardian of marriage of the Compilation of Islamic Law. This article is a literature study using descriptive-analytical research methods. The subject of this research is women's rights in the concept of marriage guardian. The approach used in the effort to critique and reconstruct women's rights as marriage guardians is the principle of gender justice. This article considers that reconstructing the idea concerning one’s right to become a marriage guardian is not something that is impossible to do. This is because the point by which only men have the right to become marriage guardian was stated by scholars, Syafi'i mazhab, was determined based on the socio-cultural conditions of the community. Back then, women were considered as lesser than men in many terms, and this was of course different from the condition of women today. That is, the parameter in determining the right of a person to be a marriage guardian is the ability to act perfectly. If so, then adult women today can become marriage guardian, as they are currently able to act perfectly (kāmil al-Ahliyyah).